PELATIHAN MENULISKREATIF UNTUK MENGEMBANGKANPOTENSI DAN KREATIVITAS ANAK - Sahabudin Sidiq (Asian Journal of Innovation and Entrepreneurship, 2013)
Writing activities, basically a good activity done by children. By writing, creativitycan be enhanced and a child is like to immerse themselves in the creative process, whichmeans the child to create something that also means asking questions, having doubts andconfusion until finally finding a solution. And when the creative process is getting trained,the child will be easier to transfer skills to other areas that also require creativesolutions, such as school or other activities. Children ages Elementary School in DusunTedunan, Tridadi Village, District Loano, Purworejo has a keen interest in reading shortstories and was interested enough to try to write a story, but unfortunately there areno means of supporting their interests. Creative Writing their training activities isexpected to motivate children to write. Because as for efforts to improve theeffectiveness of learning to write using an approach that emphasizes the importance ofthe subject of the learning process for students, the process approach and media images.